Pengaruh Pendapatan Asli Daerah, Belanja Daerah Dan Dana Alokasi Khusus Terhadap Indeks Pembangunan Manusia Pada Kabupaten/Kota Di Provinsi Sumatera Utara (Prosiding dan Call Paper Widya Wiwaha, 2023)
The purpose of this study is to analyze whether regional original revenue, regional expenditure and special allocation funds affect the human development index in regencies/cities in North Sumatera province in 2018-2020. This study used panel data regression analysis techniques with samples consisting of 25 regencies and 8 cities located in North Sumatra Province. This study conducted a chow test, a hausman test and a lagrange multiplier test in choosing a panel data regression estimation model. Based on the results of the selection test, the selected estimation model is a fixed effect model. The results of the analysis show that regional original revenue, regional expenditure and special allocation funds have a positive and significant effect on the human development index in North Sumatera Province.Therefore, it is necessary to conduct a review related to regional financial management of North Sumatra Province to focus more on areas that are still not developed, so that there is no disparity in each district and city area that still has uneven development index achievements.
Keywords: Regional original revenue; regional expenditure; Special allocation fund and human development index